The Influence of Employee Cross-Cultural and Motivation on Employee Performance Through Corporate Ethics as a Mediating Variable in DPU Bank Indonesia - Muhmmad Syafiq Maricar; Suprapto Suprapto (Dinasti Publisher, 2024)
This study aims to analyze the influence of employee cross-cultural diversity and motivation on employee performance through corporate ethics at Bank Indonesia. The population for this study consists of permanent employees of Bank Indonesia, with a sample size of 228. The data analysis method used is the Structural Equation Model-Partial Least Square (SEM-PLS). Key findings of the research indicate that cross-cultural diversity among employees positively and significantly affects employee performance. Similarly, work motivation also has a significant positive impact on employee performance. However, both cross-cultural diversity and work motivation do not show a statistically significant relationship with corporate ethics. Furthermore, corporate ethics does not have a statistically significant relationship with employee performance. Specifically, there is no significant mediating effect of corporate ethics on the relationship between cross-cultural diversity as well as work motivation and employee performance. The conclusion of this study is that although cross-cultural diversity and work motivation significantly impact employee performance, their influence through corporate ethics is not statistically significant. Therefore, organizations should focus more on creating an environment that supports cultural adaptation and motivation enhancement, while continuously evaluating and strengthening corporate ethics practices.